Two Atypical Rabbinic Mnemonic Signs Similar to Masoretic Mnemonics - Martín Contreras, Elvira (Henoch, 2020)
The use of mnemonics in both the rabbinic literature and the Masorah39 has been thoroughly explored in the past. It has been pointed out that although both fields share techniques for creating mnemonic signs, they differ widely in the use of the mnemonics and the content that must be remembered. However, an analysis of two mnemonics found in the Pesiqta de-Rav Kahana calls these differences into question. These mnemonics differ from the general pattern shown by the other mnemonics previously described in the rabbinic literature, but share some similarities with the mnemonics used in the Masorah. Moreover, Masoretic testimonies corroborating the textual information, the mnemonic signs and even the exegetical explanations given in the Pesiqta's midrashic units emphasize the similarities.